Strengthening controls on Novichoks: a family-based approach to covering A-series agents and precursors under the chemical-weapons nonproliferation regime. Issue 1 (1st June 2022) - Costanzi, Stefano; Koblentz, Gregory D.
ABSTRACT: Novichoks, also known as A-series agents, are nerve agents developed in the Soviet Union during the Cold War. Once obscure chemicals, they garnered a great deal of attention after their employment in the attempted assassinations of Sergei and Yulia Skripal in 2018 and of Alexei Navalny in 2020. Novichok agents were not originally featured in the schedules of the Chemical Weapons Convention (CWC), which are intended to support the treaty's verification regime and declaration requirements. However, following the Skripal incident, the CWC schedules were amended to include Novichok agents. Furthermore, precursors for their synthesis were added to the Australia Group's (AG) list of chemical-weapons precursors. In this article, we evaluate the recent revisions of the CWC schedules and the AG precursors list, identify the remaining weaknesses of both lists, and make recommendations for further amendments. We recommend strengthening the coverage of the CWC schedules by adding families of Novichok agents with guanidine branches. This is particularly important in light of the Navalny incident, since that incident appears to have involved a guanidine-bearing Novichok agent currently not covered by the CWC schedules. We also propose an approach to the control of Novichok precursors by the CWC and the AG based on families of chemicals rather than individually enumerated chemicals.